Long-Term Application of an Oil Residue Organic Fertilizer Improved Soil Physical Properties in the Root Zone of Jujube Trees - Huadong Zhang; Shaoliang Zhou; Weixiong Huang; Zhu Zhu; Kaixuan Li; Sanmin Sun (Agronomy)
Organic fertilizers have been widely applied in Chinese agriculture. Soil aggregate composition and pore size distribution indicate the effects of fertilizer practices on soil quality. While the effects of the long-term application of organic fertilizers on total soil pore space have been reported, few studies have examined the distribution of connected pore spaces (of critical importance for solute transport in the soil). Soil physical and chemical properties influence plant growth and soil processes. We compared the effects of organic fertilizer application (10 years, 5 years, and no application) on soil connectivity pore structures and physicochemical properties within the root zone (20–40 cm depth) around date palms through CT scanning or core samples. Specifically, when the number of years of organic fertilizer application increased, the proportion of 2–0.25 mm particle size aggregates in the soil increased, and soil connectivity pore structure became more complex and stable, with higher connectivity, pore numbers, and numbers of pore throats. The connectivity of particles of the 0–300 μm size class of pores increased and the proportion of the 500–1000 μm class of pore throats increased. Soil organic matter and enzyme activity were significantly related to soil pore structure characteristics. In conclusion, the application of organic fertilizer improved soil pore structures, and the effects became more pronounced with the increased duration of application. These results provide theoretical and practical support for the application of organic fertilizer to improve soil structures in arid areas, and the findings have significant implications for sustainable agriculture in arid and semi-arid regions.